2019
DOI: 10.1177/1073191119847762
|View full text |Cite
|
Sign up to set email alerts
|

Measurement Invariance Across Gender on the Second-Order Five-Factor Model of the German Wechsler Intelligence Scale for Children–Fifth Edition

Abstract: The present study investigated measurement invariance across gender on the German Wechsler Intelligence Scale for Children–Fifth Edition (WISC-V). The higher order model that was preferred by the test publishers was tested on a population-representative German sample of 1,411 children and adolescents aged between 6 and 16 years. Confirmatory factor analyses were conducted to test for measurement invariance. As soon as partial scalar invariance could be established by freeing nonequivalent subtest intercepts, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
21
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 85 publications
6
21
0
4
Order By: Relevance
“…An evaluation of the strong (scalar) specification suggested that both sex and diagnostic groups attained full scalar invariance, while age-groups attained partial scalar invariance. The finding of full or partial scalar invariance was consistent with previous research findings with the extended WISC-V 16 primary and secondary subtest battery (e.g., Chen et al, 2020; Pauls et al, 2019; Reynolds & Keith, 2017; Scheiber, 2016) and other intelligence tests including the Kaufman assessment battery for children, second edition (Reynolds, Scheiber, Hajovsky, Schwartz, & Kaufman, 2015; Scheiber, 2017), Woodcock-Johnson (Edwards & Oakland, 2006; Keith, 1999), and differential ability scale (Keith, Quirk, Schartzer, & Elliott, 1999). However, this is the first study to investigate invariance of the WISC-V 10-primary subtest battery across several groups (e.g., sex, age, and clinical diagnosis) with a referred sample more than double the size of the normative sample.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…An evaluation of the strong (scalar) specification suggested that both sex and diagnostic groups attained full scalar invariance, while age-groups attained partial scalar invariance. The finding of full or partial scalar invariance was consistent with previous research findings with the extended WISC-V 16 primary and secondary subtest battery (e.g., Chen et al, 2020; Pauls et al, 2019; Reynolds & Keith, 2017; Scheiber, 2016) and other intelligence tests including the Kaufman assessment battery for children, second edition (Reynolds, Scheiber, Hajovsky, Schwartz, & Kaufman, 2015; Scheiber, 2017), Woodcock-Johnson (Edwards & Oakland, 2006; Keith, 1999), and differential ability scale (Keith, Quirk, Schartzer, & Elliott, 1999). However, this is the first study to investigate invariance of the WISC-V 10-primary subtest battery across several groups (e.g., sex, age, and clinical diagnosis) with a referred sample more than double the size of the normative sample.…”
Section: Discussionsupporting
confidence: 90%
“…Invariance analyses have been conducted on the Wechsler Intelligence Scale for Children, Fifth Edition (WISC-V; Wechsler, 2014a) using the 16 primary and secondary subtest normative sample data to determine equivalence of age and sex (sic., gender) in both US standardization samples (e.g., Reynolds & Keith, 2017; Scheiber, 2016) and international samples (e.g., Chen, Zhu, Liao, & Keith, 2020; Pauls, Daseking, & Petermann, 2019). However, only one invariance study has been conducted on the 10-primary subtest battery.…”
mentioning
confidence: 99%
“…Finally, it is useful to compare the results of this of gender invariance study with those from the United States and Germany. These diverse studies show:While incongruent with the results of partial gender invariance from Germany (Pauls et al, 2019), our results supported the findings in the United States (Chen et al, 2015). Both the Taiwan and U.S. standardization data indicated full factorial invariance between boys and girls on the WISC-V higher order five-factor structure.In all three cultures, Arithmetic was cross-loaded on more than one factor; however, slightly different weightings were identified.…”
Section: Discussionsupporting
confidence: 82%
“…Both studies tested the WISC-V higher order five-factor structure in large, nationally representative samples. In 2015, Chen, Zhang, Raiford, Zhu, and Weiss reported full factorial invariance across genders in the United States, however, only partial factorial invariance was shown in Germany (Pauls et al, 2019). Pauls et al (2019) reported invariance across genders on factor pattern, factor loadings, residuals, and disturbances but subtest intercept invariance was only established for 11 of 15 subtests.…”
mentioning
confidence: 99%
See 1 more Smart Citation